2010
DOI: 10.1371/journal.pone.0015655
|View full text |Cite
|
Sign up to set email alerts
|

Soft Substrates Promote Homogeneous Self-Renewal of Embryonic Stem Cells via Downregulating Cell-Matrix Tractions

Abstract: Maintaining undifferentiated mouse embryonic stem cell (mESC) culture has been a major challenge as mESCs cultured in Leukemia Inhibitory Factor (LIF) conditions exhibit spontaneous differentiation, fluctuating expression of pluripotency genes, and genes of specialized cells. Here we show that, in sharp contrast to the mESCs seeded on the conventional rigid substrates, the mESCs cultured on the soft substrates that match the intrinsic stiffness of the mESCs and in the absence of exogenous LIF for 5 days, surpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
264
3
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(302 citation statements)
references
References 59 publications
23
264
3
8
Order By: Relevance
“…Firstly, we found that SCC substrates inhibited ESC colony spreading. Since cell spreading, stimulated by ECM components promotes ESC differentiation by the activation of integrin signalling pathways (Hayashi et al, 2007) and conversely, the reduction of cell-substrate contacts promotes selfrenewal (Chowdhury et al, 2010), we suggest that culture on the SCC substrates, which inhibit spreading, in turn repress the effectors of integrin signalling, and therefore limits differentiation. A thorough review of the effects of feature spacing on integrin adhesion by Biggs et al also suggests that features in the size range we studied may disrupt integrin binding, which is consistent with the diminished colony spreading we observed (Biggs et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Firstly, we found that SCC substrates inhibited ESC colony spreading. Since cell spreading, stimulated by ECM components promotes ESC differentiation by the activation of integrin signalling pathways (Hayashi et al, 2007) and conversely, the reduction of cell-substrate contacts promotes selfrenewal (Chowdhury et al, 2010), we suggest that culture on the SCC substrates, which inhibit spreading, in turn repress the effectors of integrin signalling, and therefore limits differentiation. A thorough review of the effects of feature spacing on integrin adhesion by Biggs et al also suggests that features in the size range we studied may disrupt integrin binding, which is consistent with the diminished colony spreading we observed (Biggs et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, mouse ESCs provide a simple assay system to evaluate the significance of the unique Rhox6 expression pattern in ESCs and PGCs. In particular, because the POU-domain transcription factor Oct3/4 (Pou5f1) is expressed in undifferentiated ESCs and PGCs (Yeom et al, 1996;Yoshimizu et al, 1999;Niwa et al, 2000;Tanaka et al, 2002), the use of a mouse ESC line that expresses enhanced green fluorescent protein (EGFP) under the Oct3/4 promoter (Walker et al, 2007;Chowdhury et al, 2010;Li et al, 2011;Tedesco et al, 2011) allows us to evaluate the pluripotency of ESCs and the differentiation of PGCs in real time. In this study, the cDNA encoding Rhox6 and short-hairpin (sh) RNA directed against Rhox6 were introduced into ESCs, although they were not found to induce the immediate differentiation of ESCs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in murine ES cells (3,4) and tissue-specific stem cells (5)(6)(7)(8)(9)(10) indicate that the adhesive and mechanical properties of the substratum used can influence cell fate decisions (11). For example, human mesenchymal stem (hMS) cells are sensitive to changes in substrate elasticity and respond by differentiating toward distinct cell lineages depending on the stiffness of the matrix (5).…”
mentioning
confidence: 99%